Observations from Implementation of the ERAS Protocol after DIEP Flap Breast Reconstruction - Haddock, Nicholas T.; Garza, Ricardo; Boyle, Carolyn E.; Teotia, Sumeet S. (Journal of Reconstructive Microsurgery, 2021)
Background The Enhanced Recovery After Surgery (ERAS) protocol is a multivariate intervention requiring the help of several departments, including anesthesia, nursing, and surgery. This study seeks to observe ERAS compliance rates and obstacles for its implementation at a single academic institution.Methods This is a retrospective study looking at patients who underwent deep inferior epigastric perforator (DIEP) flap breast reconstruction from January 2016 to September 2019. The ERAS protocol was implemented on select patients early 2017, with patients from 2016 acting as a control. Thirteen points from the protocol were identified and gathered from the patient's electronic medical record (EMR) to evaluate compliance.Results Two hundred and six patients were eligible for the study, with 67 on the control group. An average of 6.97 components were met in the pre-ERAS group. This number rose to 8.33 by the end of 2017. Compliance peaked with 10.53 components met at the beginning of 2019. The interventions most responsible for this increase were administration of preoperative medications, goal-oriented intraoperative fluid management, and administration of scheduled gabapentin postoperatively. The least met criterion was intraoperative ketamine goal of >0.2 mg/kg/h, with a maximum compliance rate of 8.69% of the time.Conclusion The introduction of new protocols can take over a year for full implementation. This is especially true for protocols as complex as an ERAS pathway. Even after years of consistent use, compliance gaps remain. Staff-, patient-, or resource-related issues are responsible for these discrepancies. It is important to identify these issues to address them and optimize patient outcomes.
Keywords: breast reconstruction; autologous breast reconstruction; free flap; deep inferior epigastric perforator; microsurgery; enhanced recovery after surgery; ERAS; enhanced recovery pathway; ERP